The successful frauditors casebook - Tickner, Peter, 1952- (John Wiley & Sons, 2012)
Learn what works well and avoid the pitfalls in the real world of fraud detection and fraud investigation. This casebook reveals how frauds and fraudsters were discovered -- and delves into the investigations that followed. Each chapter covers a particular case, analyzing the factors that allowed fraud to develop and assessing the effectiveness of the detection process and the resulting fraud investigation. Importantly, the casebook examines the steps taken by organizations to recover from the cost of fraud and the damage that fraud has caused.